Development and Characterization of an Antimicrobial Polydopamine Coating for Conservation of Humpback Whales - Tyo, Ariana; Welch, Sonja; Hennenfent, Maureen; Kord Fooroshani, Pegah; Lee, Bruce P.; Rajachar, Rupak (Frontiers in Chemistry, 2019)
Migration patterns of humpback whales have been monitored using 316L stainless steel (SS) satellite telemetry tags. The potential for tissue infection and necrosis is increased if the bacteria, naturally a part of the diverse microbiome on the skin of humpback whales, can adhere to and colonize the surface of the tags. Polydopamine (pDA) has the potential to prevent the adhesion of one of the most prevalent bacterial strains on the surface of the skin of cetaceans (Psychrobacter) through the release of hydrogen peroxide. The release of hydrogen peroxide from the pDA coatings (40M - 100M) has the ability to induce a bacteriostatic response in E. coli, a commonly used bacteria strain in antimicrobial studies and potentially P. cryohalolentis, a common humpback associated bacteria. The H2O2 dose required to induce bacteriostatic conditions in E. coli is approximately 60M and in P. cryohalolentis is 100M. Bacterial adhesion on the surface of pDA coated SS coupons was measured first using E. coli. The coating successfully prevented adhesion of E. coli on the surface of SS coupons under certain conditions (60% reduction, p <0.05) but the same was not seen with P. cryohalolentis. When coating conditions were altered (an increase in pH and temperature) the adhesion of P. cryohalolentis was reduced (80% reduction, p<0.001). Overall, the pDA coatings have the capacity to generate varying amounts of hydrogen peroxide by altering the coating conditions and have the ability to reduce bacterial adhesion on the surface of satellite telemetry tags, and therefore the potential to increase tag functional service lifetime.